Learning Environment Analysis in Increasing the Learning Spirit of PGRI Silampari University Students - Agus Susilo; Yohana Satinem; Ratna Wulan Sari; Krisna Tri Salsabilla (Yayasan Insan Mulia Bima, 2025)
This study examines the influence of the learning environment on student learning motivation at PGRI Silampari University, focusing on three dimensions: physical, social, and cultural aspects of the campus environment. The study was motivated by the phenomenon of declining learning motivation associated with an suboptimal learning environment. The objective of this research is to analyze the role of these three environmental aspects in promoting learning motivation. The method used is qualitative descriptive, with data collected through observation, in-depth interviews (with students and lecturers), and document analysis. Data were analyzed systematically through data reduction, information presentation, and verification using triangulation. The results of the study indicate that an adequate physical environment (such as comfortable classrooms, a well-equipped library, and green open spaces) enhances learning comfort. The social aspect, particularly harmonious relationships between lecturers and students as well as dynamic study groups, creates a conducive academic atmosphere. Meanwhile, a campus culture that encourages innovation and achievement through both academic and non-academic activities strengthens healthy competition. Based on these findings, the study recommends the balanced development of the three aspects of the learning environment to create an optimal educational environment for enhancing student motivation.